Incorporating circularity into digital platforms through business model innovation - Pappalardo, Alessandro (2022)
The common part covers innovation at digital payments market leader PayPal. Confronted with new threats and opportunities in the dynamic market, students analyze the situation with a comprehensive framework to reach the conclusion that business model innovation is the best option. The individual part addresses a practical research gap regarding the way digital platforms can use technology and strategy for effective circular business model innovation. The explorative research approach revealed two conjectures to guide researchers toward more applicable insights: (i) Radical technological transformation is needed to enhance data-based insights and (ii) “open-slowing” strategies facilitate reaching full circularity.